Prevalence, Indications, and Community Perceptions of Caesarean Section Delivery in Ngora District, Eastern Uganda: Mixed Method Study - Isaac Waniala; Sandra Nakiseka; Winnie Nambi; Isaac Naminya; Margret Osuban Ajeni; Jacob Iramiot; Rebecca Nekaka; Julius Nteziyaremye (Obstetrics and Gynecology International)
Background. Uganda has a high maternal mortality ratio (MMR) of 336/100,000 live births. Caesarean section is fundamental in achieving equity and equality in emergency obstetric care services. Despite it being a lifesaving intervention, it is associated with risks. There has been a surge in caesarean section rates in some areas, yet others remain underserved. Studies have shown that rates exceeding 15% do not improve maternal and neonatal morbidity and mortality. Our study aimed at determining the prevalence, indications, and community perceptions of caesarean section delivery in Eastern Uganda. Methods and Materials. It was both health facility and commuity based cross-sectional descriptive study in Ngora district, Eastern Uganda. Mixed methods of data collection were employed in which quantitative data were collected by retrospectively reviewing all charts of all the mothers that had delivered at the two comprehensive emergency obstetric care service facilities between April 2018 and March 2019. Qualitative data were collected by focus group discussions till point of saturation. Data were entered into EpiData (version 3.1) and analyzed using SPSS software (version 24). Qualitative data analysis was done by transcribing and translating into English verbatim and then analyzed into themes and subthemes with the help of NVIVO 12. Results. Of the total 2573 deliveries, 14% (357/2573) were by CS. The major single indications were obstructed labour 17.9%, fetal distress 15.3%, big baby 11.6%, and cephalopelvic disproportion (CPD) 11%. Although appreciated as lifesaving for young mothers, those with diseases and recurrent intrauterine fetal demise, others considered CS a curse, marriage-breaker, misfortune, money-maker and a sign of incompetent health workers, and being for the lazy women and the rich civil servants. The rise was also attributed to intramuscular injections and contraceptive use. Overall, vaginal delivery was the preferred route. Conclusion. Several misconceptions that could hinder access to CS were found which calls for more counseling and male involvement. Although facility based, the rate is higher than the desired 5–15%. It is higher than the projected increase of 36% by 2021. It highlights the need for male involvement during counseling and consent for CS and concerted efforts to demystify community misconceptions about women that undergo CS. These misconceptions may be a hindrance to access to CS.